(untitled) (Revista Direitos Humanos e Democracia, 2021)
HUMAN RIGHTS, MEDIA AND REFUGE: An analysis of the construction of the narrative about Venezuelan migrants in Brazil This study is based on an interest in the image of Venezuelans in Brazil, many of whom chose to request refugee status. The objective of this paper is to analyze the media representation about the Venezuelans who crossed the northern border of Brazil in recent years, starting from a specific case as a way of prompting discussions not only about representation as a form of power, but also about injustice through the operation of identity biases and stereotypes. Theoretically, we start from the relations between the politics of pity, as defined by Boltanski, and the ambivalent view of the representations of refugee and forced migration. The methodology comprises empirical research with the analysis of the period of August of 2018 as a reference to the last attacks on Venezuelans in Roraima. To do so, we selected three of the most widely circulated newspapers in the country, namely: O Globo, Folha de São Paulo and Estadão, and propose a content analysis on the main discourses articulated around the figure of the Venezuelans in the period under analysis. As a result of the analysis, we observe that the confrontations between Venezuelans and Brazilians, the increase of crime and violence and the attacks of a xenophobic nature are treated in the media in a way that refers to the threat to public safety and the weakening of the Brazilian State; and not with a focus on guaranteeing the human rights of Venezuelans who resort to the country in search of survival conditions.